Oral stress and paleodiet changes among hunter‐gatherers from Negro River (northern Patagonia, Argentina) during the late Holocene. (14th November 2019) - Flensborg, Gustavo; Serna, Alejandro; Prates, Luciano
Abstract: The objective of this work is to evaluate temporal variation of dento‐alveolar lesions in hunter‐gatherer groups who inhabited the middle course of the Negro River during the late Holocene (ca. 3000‐750 years BP) in order to discuss cultural practices and changes in the paleodiet. Caries, dental calculus, periodontal disease, periapical lesions, antemortem tooth loss, tooth wear, dislocation, and osteoarthrosic lesions in the temporomandibular joint were analysed. The sample is represented by 567 teeth and 547 alveoli, corresponding to 32 adult and subadult individuals, who were divided into two periods for comparative purposes: pre‐1000 and post‐1000 BP. The results indicate a low prevalence of oral lesions without differences between sex and age. In the pre‐1000 BP period, there is a larger frequency of antemortem tooth loss, parafunctional wear of the anterior teeth, dental dislocations, and osteoarthrosis in the mandibular condyles compared with the post‐1000 period. This tendency indicates that the individuals would have been exposed to greater stress in chewing. However, the variations were not significant, so there is no clear evidence of changes in the diet and particularly in carbohydrate and plant intake through the late Holocene. Severe tooth wear is the main factor that caused some pathologies (e.g., antemortem tooth loss), and limited the development of others (e.g., caries). The results obtained here agree with other microregions from northeastern Patagonia and differ from Humid Pampas, eastern Pampa‐Patagonian transition, and lower course of the Negro River due to differences in carbohydrate consumption in the last ca. 1000 years BP.